XRF elemental analysis of inks in South American manuscripts from 1779 to 1825 - Luízar Obregón, Celina (2021)
This work was carried out with resources from the gas canon of the Cusco Region and the support of FONDECYT—CIENCIACTIVA- CONCYTEC (Res. Dir. 016–2018-FONDECYT-DE; No Reg. 56747). / Producto elaborado en el marco del Proyecto de investigación dentro del Programa YACHAYNINCHIS WIÑARINANPAQ de la UNSAAC y CONCYTEC (FONDECYT/PROCIENCIA).